Importance performance analysis jemaah haji Kementerian Agama Kota Banjarmasin - Mardhiatin Nisa Rohama; Restu Khaliq (UIN Antasari Banjarmasin, 2019)
Professional public services are needed by the public as customers of public services, including the Hajj service. This study intends to measure the level of satisfaction of pilgrims to the quality of Hajj services in the Ministry of Religion of Banjarmasin City in 1438 H / 2017 M using the Importance Performance Analysis (IPA) method. The respondents of this study were 90 people. The results of this study indicated that the dimensions of responsiveness and assurance are the top priority for improvement. In addition there was a place of complaint for items scattered/missing goods congregation, employees/officers master the ins and outs of hajj and current issues in Saudi Arabia, fast and appropriate services in providing information on departure/calling congregation, giving health care to sick congregations, as well as facilities the complete practice of Hajj rituals were services attribute that must be improved in quality